EFFECT OF WATER MANAGEMENT PRACTICES AND NITROGEN SOURCES ON SPAD, N CONTENT AND UPTAKE IN RICE (Oryza sativa L.) - S. A. HUSSAIN, P. MADHAVI, G. JAYASREE, T. ANJAIAH G. PRATIBHA and (The Journal of Research, PJTSAU, 2020)
A field study was carried out for two years on clay loam soil during Rabi 2015-16 and 2016-17 at college farm, College of Agriculture, Rajendranagar, Hyderabad, Telangana, India with a view to study the relationship between SPAD value, plant nitrogen content and uptake. The experiment was laid out in a Split plot design under two types of water management practices i.e., Continuous flooding (CF) and alternate wetting and drying (AWD) with five treatments viz., T1- N0:P2O5 @ 60 kg ha-1: K2O @ 60 kg ha-1 (Control); T2- Nitrogen @ 120 kg ha-1(Prilled Urea): P2O5 @ 60 kg ha-1: K2O @ 60 kg ha-1 T3- Soil test based fertiliser application; T4- Nitrogen @ 60 kg ha-1+ 60 kg ha-1 through green manure and T5-Nitrification inhibitor Coated Urea. MTU-1010 variety was cultivated and recommended management practices were followed.In continuous flooding plots always 5 cm level of water was maintained, while in alternate wetting and drying, when hairline crack appeared on surface of soil, irrigation was given. Significantly higher SPAD values, N content and N uptake was recorded in the crop raised under continuous flooding over alternate drying at all crop growth stages. Among different nitrogen sources, higher SPAD and N uptake was observed with Soil test crop response (STCR) treatment. High N content was observed with green manure treated plot followed by coated urea and STCR treatment. Interaction effect of water management methods and nitrogen sources on SPAD, N content and N uptake was significant. Strong relationship between SPAD and plant N content was observed at flowering stage, whereas for SPAD and N uptake, a good correlation was noticed at harvest.